1997
DOI: 10.1046/j.1365-2648.1997.19970251175.x
|View full text |Cite
|
Sign up to set email alerts
|

Informational needs of women with a recent diagnosis of breast cancer: development and initial testing of a tool

Abstract: This study developed and tested the Toronto Informational Needs Questionnaire-Breast Cancer (TINQ-BC), a questionnaire designed to identify the information which women with a recent diagnosis of breast cancer need to deal with their illness. The 73-item questionnaire had content validity based on findings in the literature and opinions of expert oncology nurses. It was administered to 114 women with a recent diagnosis of breast cancer during chemotherapy (n = 39), radiation therapy (n = 40) or surgery (n = 35)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 27 publications
6
116
0
Order By: Relevance
“…As such, it is an empirical method of determining 'the underlying dimensionality' of a set of variables [12]. Factor analysis suggested by Galloway et al (1997) [5] for the Toronto informational Needs QuestionnaireBreast Cancer (TINQ-BC) was used in the present research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, it is an empirical method of determining 'the underlying dimensionality' of a set of variables [12]. Factor analysis suggested by Galloway et al (1997) [5] for the Toronto informational Needs QuestionnaireBreast Cancer (TINQ-BC) was used in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…In the second step, a consultative meeting was organized at which the same panel grouped the items into different subscales or domains that have been identified from literature survey [5]. Using collective professional experience, items that were thought to be repetitions and culturally inappropriate were removed by consensus.…”
Section: Development Of the Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] The results of a systematic review show that patients with fulfilled information needs have a better quality of life and less anxiety and depression. 34) Degner et al reported that newly diagnosed breast cancer patients place a high priority on information about chances of cure, spread of the disease, treatment options, family (genetic) risks, and adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Older cancer patients prefer paced information which is repeated to allow time for assimilation [22], with information provided throughout the treatment pathway as information needs change [14]. Patients' recall is impaired in lifethreatening situations [42,62], and information absorption is hindered when individuals are provided with information they find difficult or unpleasant [62] or when they are overwhelmed by the provision of excessive information in a single consultation [64].…”
Section: Pacing Of Informationmentioning
confidence: 99%